Cranberries improve postprandial glucose excursions in type 2 diabetes. Issue 9 (27th July 2017) - Schell, Jace; Betts, Nancy M.; Foster, Megan; Scofield, R. Hal; Basu, Arpita
Abstract : An overview of the role of dried cranberries in reducing postprandial hyperglycemia and inflammation in type 2 diabetes and the subsequent risks of vascular complications. Abstract : Recent research supports a favorable role of cranberries on cardiometabolic health. Postprandial metabolism, especially hyperglycemia, has been shown to be an independent cardiovascular risk and few clinical studies have reported the role of berries in improving postprandial dysmetabolism. We investigated the postprandial effects of dried cranberries following a high-fat breakfast challenge in obese participants with type 2 diabetes (T2DM), in a randomized crossover trial. Blood draw and vascular measurements were conducted at fasting, 1, 2 and 4 hours (h), following the consumption of a fast-food style high-fat breakfast (70 g fat, 974 kcal) with or without cranberries (40 g). Analyses of our data ( n = 25; BMI (kg m −2 ) (mean ± s.d.) = 39.5 ± 6.5; age (years) = 56 ± 6) revealed that postprandial increases in glucose were significantly lower in the cranberry vs. control at 2 & 4 h ( p < 0.05). No significant differences were noted in insulin, insulin resistance evaluated by homeostasis model assessment, lipid profiles and blood pressure between the cranberry and control groups. Among the biomarkers of inflammation and oxidation, postprandial serum interleukin-18 and malondialdehyde were significantly lower at 4 h, and serum total nitrite was higher at 2 h in the cranberry vs. control group (all p < 0.05). No effects were noted on C-reactive protein or interlukin-6. Overall, dietary cranberries had notable effects in improving high-fat breakfast induced postprandial glucose and selected biomarkers of inflammation and oxidation in participants with T2DM. These findings provide evidence that adding whole cranberries to a high-fat meal may improve postprandial blood glucose management and warrant further investigation.